Bifidobacterium animalis subsp. lactis decreases urinary oxalate excretion in a mouse model of primary hyperoxaluria - Klimesova, Klara; Whittamore, Jonathan M.; Hatch, Marguerite (Urolithiasis, 2015)
Hyperoxaluria significantly increases the risk of calcium oxalate kidney stone formation. Since several bacteria have been shown to metabolize oxalate in vitro, including probiotic bifidobacteria, we focused on the efficiency and possible mechanisms by which bifidobacteria can influence oxalate handling in vivo, especially in the intestines, and compared these results with the reported effects of Oxalobacter formigenes . Bifidobacterium animalis subsp. lactis DSM 10140 and B. adolescentis ATCC 15703 were administered to wild-type (WT) mice and to mice deficient in the hepatic enzyme alanine-glyoxylate aminotransferase ( Agxt −/− , a mouse model of Primary Hyperoxaluria) that were fed an oxalate-supplemented diet. The administration of B. animalis subsp. lactis led to a significant decrease in urinary oxalate excretion in WT and Agxt −/− mice when compared to treatment with B. adolescentis . Detection of B. animalis subsp. lactis in feces revealed that 3 weeks after oral gavage with the bacteria 64 % of WT mice, but only 37 % of Agxt −/− mice were colonized. Examining intestinal oxalate fluxes showed there were no significant changes to net oxalate secretion in colonized animals and were therefore not associated with the changes in urinary oxalate excretion. These results indicate that colonization with B. animalis subsp. lactis decreased urinary oxalate excretion by degrading dietary oxalate thus limiting its absorption across the intestine but it did not promote enteric oxalate excretion as reported for O. formigenes. Preventive or therapeutic administration of B. animalis subsp. lactis appears to have some potential to beneficially influence dietary hyperoxaluria in mice.